The Implementation of Reciprocal Teaching Method (RTM) in Developing Reading Comprehension of the Second Grade Students of SMAN 2 Bantaeng - Andi Bulkis Maghfirah Mannong (INTERACTION: Jurnal Pendidikan Bahasa, 2018)
This research is conducted to find out : (1) whether (or not) the implementation of Reciprocal Teaching Method develop the reading comprehension of the second grade students of SMAN 2 Bantaeng, and (2) to find out whether (or not) the use of Reciprocal Teaching Method interest the second grade students of SMAN 2 Bantaeng.This research employed a quasi-experimental. The population of this study was second grade students of SMAN 2 Bantaeng. This research uses cluster random sampling technique. Samples of students included in two classes; 25 students in the experimental class and 25 students in the control class. Data were analyzed SPSS version 20.0. This study shows an increase in learning outcomes of the students in the classroom Improved student learning outcomes from posttest of control with an average score of 80.23> 76.40-test level of significance of 0.05 where the value of the value is higher than the significant level (0,000 <0 , 05). The average value of student interest in the experimental class is 65.14 where the value of standard deviation is 9,078 and categorized as interested. Thus, it can be concluded that the use of RTM improves reading comprehension of students and students who are interested in learning reading comprehension.